First report of overwintering tadpoles in the endemic Italian agile frog Rana latastei - Andrea Melotto; Antonio Serafino Melotto; Gentile Francesco Ficetola; Raoul Manenti; Mattia Falaschi (Acta Herpetologica)
Climate change is affecting organism seasonality patterns, and this can drive phenological shifts for key traits, including breeding activity. Here we report a first record of overwintering tadpoles of the Italian agile frog (Rana latastei), a threatened endemic species of Northern Italy. This species usually breeds between late January and April, with tadpoles reaching metamorphosis by early summer. In February 2025, together with the first freshly-laid egg-clutches of the season, several large-sized tadpoles were found in one reproductive site of R. latastei in Como province. A few days after hatching, six individuals from newly hatched tadpole cohorts and six individuals from large-sized cohorts were captured, photographed and measured. Concurrently, a newly metamorphosed froglet was found. Results from morphological inspections revealed that  individuals showed typical traits of R. latastei. Moreover, while newly hatched tadpoles were at development Gosner’s stages 25-26, large cohort individuals were visibly bigger and at late development stage, which was not compatible with the classical late winter breeding timing of this species. Our study shows for the first time a case of overwintering in R. latastei, suggesting shifts in this frog development trajectory (prolonged larval time) or breeding habits (autumnal reproduction) may be occurring.  While mechanisms behind this unusual observation have to be ascertained, such a phenological shift might have been favoured by variation in climatic regime.